2017
DOI: 10.3390/w9060383
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Terrestrial and Aquatic Environmental Controls of Riverine Dissolved Organic Carbon in the Conterminous United States

Abstract: Analyses of environmental controls on riverine carbon fluxes are critical for improved understanding of the mechanisms regulating carbon cycling along the terrestrial-aquatic continuum.Here, we compile and analyze riverine dissolved organic carbon (DOC) concentration data from 1402 United States Geological Survey (USGS) gauge stations to examine the spatial variability and environmental controls of DOC concentrations in the United States (U.S.) surface waters. DOC concentrations exhibit high spatial variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 76 publications
2
8
1
Order By: Relevance
“…The comparison of sites in urban areas (Bolham vs. Exe at Tiverton comparison) did not prove to offer significant contributions to DOC concentration, despite the potential for urban runoff and sewage effluent to influence this (Noacco et al, 2017) and inclusion in the ALM results. This is also contrary to the findings of Yang et al, (2017) who noted a significant effect of urban extent on DOC concentrations in their study of 1,402 sites across the USA. This could perhaps be explained by the relatively small size of Tiverton, the main conurbation upstream of the treatment works, which has a population of 21,335 (UK census 2011).…”
Section: Catchment Surveycontrasting
confidence: 99%
See 2 more Smart Citations
“…The comparison of sites in urban areas (Bolham vs. Exe at Tiverton comparison) did not prove to offer significant contributions to DOC concentration, despite the potential for urban runoff and sewage effluent to influence this (Noacco et al, 2017) and inclusion in the ALM results. This is also contrary to the findings of Yang et al, (2017) who noted a significant effect of urban extent on DOC concentrations in their study of 1,402 sites across the USA. This could perhaps be explained by the relatively small size of Tiverton, the main conurbation upstream of the treatment works, which has a population of 21,335 (UK census 2011).…”
Section: Catchment Surveycontrasting
confidence: 99%
“…This provides evidence for hypothesis b), that there are significant sources of Work in nearby catchments in the south-west of England has also suggested that baseflow DOC concentrations can be higher in agricultural catchments than in semi-natural ones (Glendell and Brazier, 2014) due to the addition agricultural amendments to the soil and artificial fertiliser altering the rate of carbon turnover (Chantigny, 2003). These findings agree with other published work suggesting that DOC quantity and quality can be influenced by the extent of riparian wetlands, woodlands and cropland (Wilson and Xenopoulos, 2008;Yang et al, 2017). These data also add weight to the growing need for an understanding of how agriculturally-derived DOC affects catchment carbon budgets, how this may change in the future and how this can be managed for positive water quality outcomes (e.g.…”
Section: Catchment Surveysupporting
confidence: 87%
See 1 more Smart Citation
“…To test the role OM chemistry as a key regulator of aerobic metabolism, we incubated sediments with thermodynamically distinct N-bearing or N-free OM treatments at concentrations commonly observed in freshwater systems (from 0.3 to 9 mg C L −1 , Supplementary Table 1) 12,24,25 . We inferred carbon limitation at low treatment concentrations (< 3 mg C L −1 ) because sediments were collected from a low carbon area (%C < 0.6 as previously discussed in Graham et al 11 ) with observed C:N < 5 11 which is typically associated with carbon limitation 26,27 .…”
Section: Thermodynamic Regulation Of Aerobic Respirationmentioning
confidence: 99%
“…Continental margin sediments contain more than 90% of the carbon buried in the ocean, and the estuary coastal zone, as a sensitive exchange zone for sea-land carbon pools, effectively indicates that the global carbon cycle process is driven by sea level changes [1,2]. However, as an open system, the biogeochemical signals of coasts are complex due to the influence of multiple natural factors (such as global coastline and paleoclimate changes) and the interference of human activities [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%